The Nearctic genera of Agathidinae (Hymenoptera: Braconidae) with a phylogenetic analysis, illustrated generic key, and the description of three new genera - Sharkey, Michael J.; Chapman, Eric G. (Zootaxa, 2015)
The genera of Nearctic Agathidinae are revised based on a phylogenetic analysis of COI and 28S sequence data; 151 ingroup taxa are included. Three new genera are proposed, i.e., Aphelagathis Sharkey n. gen., Pneumagathis Sharkey n. gen. and Gelastagathis Sharkey n. gen.. The enigmatic species Agathis verticalis Cresson is identified and placed in Aphelagathis, Aphelagathis verticalis (Cresson) n. comb., and a neotype for the species is designated. Two species are described, i.e., Gelastagathis grisselli Sharkey n. sp. and G. frosti Sharkey n. sp. Two new combinations are proposed, Bassus spiracularis Muesebeck and Bassus brooksi Sharkey are transferred to Pneumagathis, Pneumagathis spiracularis (Muesebeck) n. comb., Pneumagathis brooksi (Sharkey) n. comb. An illustrated key to the Nearctic genera of Agathidinae is provided.